Promoting Canadian Student Outbound Mobility: Analysis of Internationalization Policies - Shuai Yu (Canadian Society for Studies in Education, 2023)
This study examines how internationalization policies of Canadian higher education support student outbound mobility. Applying the Global Higher Education Matrix (Jones, 2008) and the four approaches to internationalization (Knight, 1997; Zha, 2003), I collected and analyzed the international strategies implemented at the national, provincial, and institutional levels. The findings demonstrate that the current international strategies and policies support outbound student mobility from four aspects: providing financial assistance, increasing the availability and benefits of international learning opportunities, building capacities, and forming or reinforcing partnerships and collaboration. Examining international education strategies contributes to understanding the current context of Canadian student outbound mobility. Furthermore, it helps policymakers and stakeholders (institutions, administrative staff, Canadian students, and faculty members) to understand the deficiencies of the current strategies and to inform the future development of international education policies and internationalization strategies regarding outbound student mobility.